Integration of Problem-Solving-Based E-Modules in Physics Learning to Enhance the Creativity and Understanding of Engineering Students - Aflaha, Dwi Sari Ida (Universitas Syiah Kuala, 2025)
In the era of Industry 4.0, higher education must not only strengthen students conceptual understanding but also foster creative and problem-solving skills, especially among engineering students who often face difficulties in learning abstract physics concepts. This study aims to develop and evaluate the effectiveness of a problem-solving-based electronic module (e-module) to enhance engineering students creativity and conceptual understanding in physics learning. Using a qualitative library research design, this study synthesizes theories and findings from national and international publications between 2019 and 2025. Data were analyzed through content analysis to identify relationships between problem-solving-based e-modules, creativity, and conceptual mastery. The results reveal that integrating problem-solving stagesproblem identification, hypothesis formulation, model construction, testing, and reflectioninto e-modules significantly improves creativity indicators such as fluency, flexibility, and originality, as well as conceptual comprehension of physical principles. Expert validation confirmed the modules high feasibility and practicality, with students reporting improved motivation and engagement. Furthermore, the inclusion of real-world engineering scenarios and interactive simulations successfully bridged the gap between theoretical physics and its practical applications. Overall, the findings highlight that problem-solving-based e-modules serve as an effective pedagogical innovation for promoting active, creative, and conceptual learning in physics education for engineering students.